Mediterranean Diet and Olive Oil Redox Interactions on Lactate Dehydrogenase Mediated by Gut Oscillibacter in Patients with Long-COVID-19 Syndrome - Amanda Cuevas-Sierra; Victor de la O; Andrea Higuera-Gómez; Lourdes Chero-Sandoval; Begoña de Cuevillas; María Martínez-Urbistondo; Victor Moreno-Torres; Ilduara Pintos-Pascual; Raquel Castejón; J. Alfredo Martínez (Antioxidants)
Chronic viral inflammation is associated with oxidative stress and changes in gut microbiota. The Mediterranean diet (MD), with recognized anti-inflammatory and antioxidant properties, modulates gut microorganisms, specifically on the interaction between extra virgin olive oil, a key component of the MD with well-documented antioxidant effects. This study investigated the influence of adherence to MD and antioxidant-rich foods (extra virgin olive oil) on biochemical, inflammatory, and microbiota profiles in patients with chronic inflammation defined as a prolonged inflammatory response due to immune dysregulation following the acute phase of the viral infection. Participants were classified into low (n = 54) and high (n = 134) MD adherence groups (cut-off of 7 points based on previous studies utilizing the same threshold in the assessment of MD adherence). Gut microbiota was sequenced using the 16S technique, and the adherence to MD was assessed using a validated questionnaire for a Spanish population. High adherence to the MD was linked to significant improvements in inflammatory and oxidative stress markers, including reductions in LDL-cholesterol, glucose, and lactate dehydrogenase (LDH) levels, an indicative of redox balance, as well as a significant higher consumption of antioxidant foods. Moreover, gut microbiota analysis revealed distinct compositional shifts and a lower abundance of the Oscillibacter genus in the high adherence group. Notably, a significant interaction was observed between MD adherence and extra virgin olive oil consumption, with Oscillibacter abundance influencing LDH levels, suggesting that the MD antioxidant properties may modulate inflammation through gut microbiota-mediated mechanisms. These findings provide new evidence that adherence to the Mediterranean diet can reduce inflammatory markers in patients with long-COVID-19, a population that has not been extensively studied, while also highlighting the potential role of the bacterial genus Oscillibacter in modulating this effect.